Studi Perancangan Jaringan Worldwide Interoperability For Microwave Access (Wimax) Di Area Banyumas - Alfin Hikmaturokhman; Anggun Fitrian Isnawati; Ike Lestari (JURNAL INFOTEL, 2012)
At present the need for higher internet connection along with the age which is growing so fast. Then there is the latest breakthrough in telecomunications that is WiMAX technology is a wireless broadband technology reffered the IEEE 802.16 standard. WiMAX technology comes with a network of excellence in aspects of data access speed, wide area coverage and the presence of QoS is can allocate frequencies in accordance with user needs using OFDM technology. WiMAX technology can reach area far as 50 kilometers, also allows user equipment (customer premise equipment or CPE) to get a broadband connection without having a direct path (non line of sight, NLOS) to the base station (BS) and provides a total data rate of up to 75 Mbps. Results of this Final project assumed that the area where will be design is Banyumas district. Then final project results of the PRX -100.31 dB; the Total Margin of 23.56 dB; Path los of 134.5 dB; gamma (?) of 4.375; Frequency correction factor (?PLf) of 0,36; antenna correction factor (?PLh) is -3,25; Radius Cells (d) is approximately 1995 meters; area of cell is at 10,34010495 km2 and the number of cells 133